Republic of Timor-Leste : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Timor-Leste. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses recent economic developments, economic outlook, and risks in Timor-Leste. Growth has moderated while inflation has fallen sharply. Owing to a sharp fall in oil revenues and large development needs, Timor-Leste is facing difficult policy challenges. According to industry estimates, unless new oil reserves are developed, oil production is expected to decline further and cease by 2023. Prioritization of government expenditures to facilitate high-return infrastructure investments is key in tandem with structural reforms that catalyze nonoil private sector growth. The 2016 budget outlined a significant scaling up of the public investment in 2017-19, which will strain fiscal sustainability.